ANALISIS BIAYA DAN WAKTU PADA PROYEK PENINGKATAN JALAN DENGAN METODE EARNED VALUE - Fardila, Dinda; R Kamagi, Siti Nurholisa; Ali Topan, Paris; Husainy, Zainuddin (Hexagon Jurnal Teknik dan Sains, 2024)
Cost and time are important variables in a construction project. Significant cost and time deviations can indicate poor project management, so there is a need for evaluation and control regarding this matter. In this research, researchers evaluated costs and time using the Earned Value Concept method. Performance evaluation of time and cost was carried out using Microsoft Project. Cost performance using the Earned Value Method means that there is a cost overrun of IDR 1,206,432.85 from the total construction budget plan (overbudget). This is shown by the EAC (Estimate to Complete) value of IDR 11,536,477,946.05 which is greater than the BAC (Budgeted All Construction) value of IDR 11,535,271,513. Performance when using the Earned Value Method has SV values ??in the July-October period showing positive values, namely IDR 175,140,527.07, IDR 175,138,345.20, IDR 175,140,527.07, IDR 32,838,848.83, this value shows that the project was realized faster than planned. Performance based on the schedule productivity index (SPI) in the July period has a value of 1.037894631, August has a value of 1.02648206, September has a value of 1.019104588, and October has a value of 1.002926831. This SPI value shows >1, meaning that the realized work productivity is carried out faster than the planned schedule.